Effects of umbilical cord mesenchymal stem cells on expression of CYR61, FSH and AMH in mice with premature ovarian failure - Jie, He; Jinxiang, Wang; Ye, Li; Jing, Zhao; Xiangqing, Zhu; Jinxiu, Hu; Zian, Li; Xinghua, Pan (Cellular and Molecular Biology, 2022)
The aim of this study was to objective to investigate the effects of umbilical cord mesenchymal stem cells on the expression of CYR61, FSH and AMH in mice with premature ovarian failure. For this purpose, thirty SPF female SD mice were selected as the research object, 10 of which were control group, namely group α, and 20 mice with premature ovarian failure model were established by cyclophosphamide. The mice were divided into model group, namely β group and the umbilical cord mesenchymal stem cell transplantation group (γ group), with 10 mice in each group. ELSA method was used to determine the levels of follicle-stimulating hormone (FSH), Luteinizing hormone (LH), estradiol (Estradiol) in serum. The changes of E2, Antimullerian hormone (AMH) and cysteine-rich protein 61 in ovarian tissues were determined by the protein imprinting method. Connective tissue growth factor (CTGF) and caspase-3 protein expression. Results showed that in fertility rate, γ group > α group > β group, the difference was statistically significant (P<0.05), in litter size, α group > γ group > β group, the difference was statistically significant (P<0.05). The levels of serum E2 and AMH in α group > γ group > β group, and the levels of serum FSH and LH in β group > γ group > α group were statistically significant (P<0.05). The growth follicles were α group > γ group > β group, and the atresia follicles were β group > γ group > α group, and there was a statistical difference among all groups (P<0.05). There was no difference in luteal number among the three groups (P>0.05). In terms of CYR61 and CTGF protein expression, α group > γ group > β group, and in terms of caspase-3, β group > γ group > α group had statistical significance (P<0.05). It is concluded that intervention with umbilical cord mesenchymal stem cells can significantly improve the expression levels of CYR61 and AMH, reduce the level of FSH, promote cell survival, improve the reproductive quality of mice, and restore the physiological function of the ovary. It is feasible to treat premature ovarian failure with umbilical cord mesenchymal stem cells.